Drug-lnduced Esophagitis in a Tertiary Care Hospital - Haque, MA; Alim, MA; Mahmood, I; Chowdhury, MM Hoque (TAJ: Journal of Teachers Association, 2009)
Drug induced esophagitis, also known as pill-induced esophagitis or drug-induced esophageal injury, is uncommonly encountered in clinical practice. This observational study was jointly carried out by the Department of Medicine and Department of Gastroenterology, Rajshahi Medical College, from January 2005 to December 2009. Total number of patients included was 32. Patients who presented with history of odynophagia and chest pain after ingesting some medications and having endoscopic evidence of esophagitis were included in this study. Out of 32 patients 17 were female and 15 were male (F: M=1.1:1). Mean age of the patients were 36.7±8.5 years. Doxycycline was the drug most commonly associated with esophagitis, 25 cases (78.1%) had doxycycline induced esophagitis. Other drugs were tetracycline in 3 cases (9.4%), alendronate in 1 case (3.1%), ciprofloxacin in 1 case (3.1%), paracetamol in 1 case (3.1%), and naproxen in 1 case (3.1%), Increased awareness among the physicians and patient education can prevent this distressing clinical condition. TAJ 2009; 22(1): 235-238